Air-side Thermal-hydraulic Analysis and Parametric Optimization for Vertical-fin Microchannel Heat Exchanger - Zhao Rijing; Wei Xinghua; Huang Dong; Li Feng; Zhao Yongfeng (Zhileng xuebao)
Vertical-fin microchannel heat exchangers (VMHXs) have efficient thermal-hydraulic performance and favorable drainage performance, such that they are capable of being utilized in air source heat pumps under wide operating conditions. In this study, a CFD (computational fluid dynamics) model was used to analyze the air-side thermal-hydraulic performance of VMHXs under dry conditions. The model was verified using experimental results with an error of less than 20%. Subsequently, the sequence and connection of waves and louvers on composite fins were compared, and the effects of fin pitch, fin length, tube pitch, and fin thickness were investigated. Finally, parametric optimization was conducted using the Taguchi method. The results show that under constant pumping power, the heat transfer enhancement of the composite fin with the front louver fin and the reversely connected rear wavy fin is the best. When the comprehensive index performance evaluation criterion (Pec) was used to evaluate the performance of the VMHXs, the tube pitch and fin length were determined as the main influencing factors. Within the range of parameters practically available, the best performance is obtained by a combination of 1.8 mm fin pitch, 25.6 mm fin length, 12.0 mm flat tube pitch, and 0.12 mm fin thickness.